SHORT STORIES: THE POWERFUL MEDIA TO FOSTER STUDENTSâ VOCABULARY MASTERY IN READING - Agung, Guritno (Institut Agama Islam Negeri Palopo, 2017)
Vocabulary is very fundamental aspect in language learning. Even, it becomes a key to master a language. The younger people learn the language, the faster they will master it. There are so many materials and media to gain vocabulary. One of them is by reading short story. In fact, it has many advantages when it applies as the media in language learning. This article conveys a study about how the use of short story to foster studentsâ vocabulary mastery in reading and how significant of short story as the media in language learning. This study uses the model of action research which involves thirty-eight students of MTsN 2 Mataram, West Nusa Tenggara as the subject of the research. It consists of three cycles, and each cycle has 4 meetings. The data are populated from tests (pre-test and post-tests). As the result, the use of short stories is able to increase the studentsâ psychological aspect and the classroom climate. The students are become more excited, enthusiastic, and active in the learning process. This then makes the classroom climate more alive, and it is finally able to foster their ability in vocabulary mastery in reading. Moreover, this study shows the significant improvement of the studentsâ vocabulary mastery. At the end of the cycle, the students have met at least the minimum score of 7.00 standard of minimum completeness in the four areas of spelling, pronunciation, meaning, and the use of the words.Â